Study of aluminum/kevlar fiber composite laminate with and without TiC nanoparticle impregnation and aluminum/carbon fiber composite laminate for anti-ballistic materials - Benediktus Madika; Anne Z. Syahrial (International Journal of Lightweight Materials and Manufacture, 2024)
Numerous studies have investigated the advantages of using composite laminates made of both metals and fibers, which include being able to sustain heavier loads, having better resistance to impacts, and being more durable, while also being lightweight. In this particular study, we utilized the hand lay-up method to create composite laminates consisting of three layers of aluminum alloy and 60 layers of fiber. We tested three different types of aluminum alloy (Al-2024, Al-5052, and Al-7075) and two types of fiber (kevlar and carbon), which were divided into three categories: kevlar fibers, TiC nanoparticle-impregnated kevlar fibers and carbon fibers. We then combined each type of fiber with each type of aluminum alloy to make nine distinct composite laminates. To determine the mechanical properties of the laminates, we used a rule-of-mixture formula. Our research revealed that kevlar fibers had a more significant impact on increasing the yield strength and ultimate tensile strength of the composite laminates than carbon fibers. However, carbon fibers have a greater effect on the modulus of elasticity of the composite. Among all types of aluminum, Al-2024 provides the highest mechanical properties for composite laminates. However, impregnating kevlar fibers with TiC nanoparticles did not enhance the anti-ballistic performance of composite laminates. Consequently, composite laminate that consists of Al-2024 and carbon fibers exhibits the best mechanical properties and anti-ballistic performance, making them the ideal choice for anti-ballistic applications.